Comparative Review of Informed Consent as a Legal Safeguard in Healthcare: Perspectives from Indonesia and Others Countries - Firma, Fuji Restu; Jusri, Elim; Sapsudin, Asep (LifeSciFi, 2025)
Informed consent serves as a fundamental ethical and legal mechanism to uphold patient autonomy and safeguard against medical malpractice. This evolving concept provides an opportunity to assess the weaknesses and effectiveness of informed consent mechanisms as a form of legal protection in Indonesia, particularly in comparison to the legal systems of other countries. This paper aims to compare the role of informed consent as a legal safeguard in healthcare services in Indonesia and other countries. This study employed a comparative legal research method using both normative-comparative and functional approaches, supported by literature searches across four major electronic databases. The included materials consist of peer-reviewed empirical studies, legal analyses, policy reports, and case studies. In Indonesia, informed consent is governed by various legal instruments, including the newly enacted Law No. 17 of 2023. However, implementation faces challenges related to cultural values, paternalistic practices, and limited health literacy. In comparison, systems in the UK, Germany, and the US emphasize individual autonomy and standardized documentation, whereas Indonesia continues to struggle with systemic and socio-cultural barriers that compromise consent quality. In many developing countries, collective decision-making norms and resource constraints further hinder compliance with international standards. Meanwhile, developed countries face challenges related to complexity, variability in practice, and the influence of advanced technologies on patient comprehension. Informed consent is a vital legal instrument in healthcare, but its implementation is heavily influenced by the legal structure, cultural context, and institutional capacity of each country. A culturally adaptive approach to informed consent, alongside capacity strengthening, simplification of informational materials, and the use of communication technologies, is essential to ensure ethically sound and legally effective patient protection.